COVID -19 AND THE PARALYSATION OF WOMEN LIVELIHOODS IN MICRO-ENTERPRISES IN MASVINGO URBAN, ZIMBABWE (American International Journal of Humanities, Arts and Social Sciences, 2020)
Covid-19 has fast become a global catastrophic pandemic affecting all facets of life, including people’s livelihoods. Despite the devastating impact COVID-19 has caused across the globe, little has been researched on how lockdown intervention measures have affected livelihoods of entrepreneurial women. This study assesses how the conditions characterising the COVID-19 induced lockdown affected the livelihoods of Small and Medium Enterprises (SMEs) entrepreneurial women in the Masvingo Province of Zimbabwe. The study reveals that COVID-19 lockdown in Zimbabwe was (and continues to be) marred with enforced restrictions on women in the informal sector. Women in the urban areas were the most affected. The vulnerability context among urban women was characterised by shock, stress and restlessness. Based on findings of this study, we advance that COVID-19 induced lockdown paralysed entrepreneurial women’s capital assets thereby militating against their self-sustenance, self-reliance and advancement. The closure of markets, mobility permits, corruption on COVID-19 relief cash transfer and subsidised mealie-meal worsened the entrepreneurial women’s shocks, stresses and restlessness. We therefore conclude that the impact of COVID-19 has not only compromised nations’ food security and health systems, but most importantly paralysed entrepreneurial women’s livelihoods, yet women in the African context, musha mukadzi – without a mother there is no home.